Pengaruh Edukasi Qr Code Terhadap Literasi Anemia Remaja Putri Di Mas Aisyiyah Medan - Nelly Rustianti; Ni Ketut Sujati; Halimatussakdiyah Lubis (Barongko: Jurnal Ilmu Kesehatan, 2026)
Anemia among adolescent girls remains an unresolved public health and nutrition problem in Indonesia, contributing to morbidity risk during the productive years and to the intergenerational cycle of stunting. Low anemia literacy is suspected to be one of the determinant factors influencing the high prevalence of anemia among adolescent girls. This study aimed to analyze the effect of QR Code-based education on the level of anemia literacy among adolescent girls at MAS Aisyiyah Medan. This quantitative study used a quasi-experimental one group pretest-posttest design, conducted from March to May 2026 with 50 respondents selected through total sampling. Data were analyzed univariately and bivariately using the Wilcoxon Signed Rank Test. The results showed a significant increase in anemia literacy scores after the QR Code education intervention (p = 0.000; p<0.05). It is concluded that QR Code-based education effectively improves anemia literacy among adolescent girls and can be recommended as an interactive, low-cost health promotion medium integrated into school health programs (UKS/M).